2001
DOI: 10.1359/jbmr.2001.16.4.782
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids Reduce Bone Mineral Density in Early Postmenopausal but Not Premenopausal Asthmatic Women

Abstract: Inhaled corticosteroids are widely used in the treatment of bronchial asthma, but it is still uncertain whether long-term use of the inhaled corticosteroids affects bone metabolism in asthmatic patients. In this study, we examined the effect of inhaled beclomethasone dipropionate (BDP) on bone mineral density (BMD) and biochemical markers of bone metabolism in pre-and early postmenopausal asthmatic women. Thirty-six (17 premenopausal and 19 early postmenopausal) asthmatic women and 45 healthy control (24 preme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 30 publications
0
25
3
1
Order By: Relevance
“…In conclusion, many studies have reported unfavourable systemic effects of ISC, although they are the mainstay of long-term asthma treatment [3][4][5]. In contrast, we were able to show that carotid atherosclerosis was less severe in asthmatic patients treated with ICS than in control subjects.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In conclusion, many studies have reported unfavourable systemic effects of ISC, although they are the mainstay of long-term asthma treatment [3][4][5]. In contrast, we were able to show that carotid atherosclerosis was less severe in asthmatic patients treated with ICS than in control subjects.…”
Section: Discussioncontrasting
confidence: 52%
“…Besides the direct inhibitory effects of corticosteroids on the expression of vascular adhesion molecules [10,11], they also show acute cardiovascular effects through nontranscriptional activation of endothelial nitric oxide synthase [31]. Relatively small amounts of ICS are absorbed into the circulation, which sometimes results in hypothalamic-pituitary-adrenal axis suppression, abnormal bone metabolism and cataracts [4,5]. There is no information about the effects of ICS on the cells that make up vessel walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior fractures are important risk factors for low BMD and fracture in adults (31,32), and the long-term use of corticosteroid inhalers in the treatment of asthma is associated with bone loss in a dose-related fashion (33)(34)(35)(36)(37). However, the effect of long-term therapy of ICS on bone mass in children and youth is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The BMDin humans decreases with increasing age, with decrease being particularly marked in postmenopausal women. Arecent study has demonstrated that ICS treatments decrease the BMDin postmenopausal women (17). Thus, BMDin older asthmatics, especially women, should be measured regularly and osteoporosis in these patients needs to be treated adequately.…”
Section: Discussionmentioning
confidence: 99%